Epidemiological Surveillance of Teen Birth Rates in the United States 2006-2012 [19A]. Issue 1 (May 2017) - Amin, Raid; DeCesare, Julie; Roussos-Ross, Dikea
Abstract : INTRODUCTION: To investigate the geographical variation in the average teen birth rates by county between 2006 and 2012 in the contiguous US. METHODS: SaTScan™, a software for disease surveillance and spatial cluster analysis was used to evaluate the spatial variation in teen birth rates and identify clusters with elevated relative risk. The analyses were first completed using unadjusted teen birth data. The data was then adjusted for percent poverty and percent high school diploma. RESULTS: The southern half of the US harbored most of the teen birth clusters in the unadjusted data set, and represented seven of the top ten cluster areas. When adjusting for poverty and high school diploma rate, the south still was the most represented geographical area, harboring four of the top ten clusters. CONCLUSION: Despite an overall national decline in the teen birth rate, clusters of elevated teen birth rates remain. These clusters are not random, and remain higher than expected when adjusted for poverty and education. This data set will provide a framework to focus targeted intervention implementation in order to reduce teen birth rates in this high risk population.